2008
DOI: 10.1016/j.neuroscience.2008.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Progressive synaptic pathology of motor cortical neurons in a BAC transgenic mouse model of Huntington's disease

Abstract: Huntington’s disease (HD) is a neurodegenerative disorder caused by a polyglutamine repeat expansion in huntingtin. A newly developed BAC transgenic mouse model (BACHD) reproduces phenotypic features of HD including predominantly neuropil associated protein aggregation and progressive motor dysfunction with selective neurodegeneration. Motor dysfunction has been shown to precede neuropathology in BACHD mice. We therefore investigated the progression of synaptic pathology in pyramidal cells and interneurons of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 65 publications
4
62
0
Order By: Relevance
“…Cell-nonautonomous effects of afferent sensory and cortical projections on the toxicity and degeneration of the motor neuron has been described recently in mouse models of human ALS, spinal muscular atrophy, and Huntington disease (47)(48)(49). If protein folding homeostasis in diverse tissues of other metazoans is under the regulation of sensory neuronal modalities as we have described for C. elegans, this would suggest that another method for treatment of human conformational diseases could involve modulation of neurosensory systems.…”
Section: Discussionmentioning
confidence: 79%
“…Cell-nonautonomous effects of afferent sensory and cortical projections on the toxicity and degeneration of the motor neuron has been described recently in mouse models of human ALS, spinal muscular atrophy, and Huntington disease (47)(48)(49). If protein folding homeostasis in diverse tissues of other metazoans is under the regulation of sensory neuronal modalities as we have described for C. elegans, this would suggest that another method for treatment of human conformational diseases could involve modulation of neurosensory systems.…”
Section: Discussionmentioning
confidence: 79%
“…In our hands, the failure of LTP in R6/1 and R6/1-89Q slices might also reflect a higher threshold for LTP induction caused by a greater level of magnesium voltage-dependent blockade of NMDA channels, a phenomenon that might be sensitive to postsynaptic D 1 receptor modulation. Similarly, it has been reported that motor cortical neurones in BAC transgenic mouse model of HD exhibit a progressive reduction in excitability [48] .…”
Section: Discussionmentioning
confidence: 82%
“…These results suggest that the beneficial effects of decreasing aak-2 activity may be through improving the functioning of neurons under conditions of stress and proteotoxicity. Several reports highlight the presence of neuronal dysfunction before neuronal death in several models of neurodegenerative disease, such as ALS (Gould et al, 2006;Ilieva et al, 2008), spinal muscular atrophy (Mentis et al, 2011), spinocerebellar ataxia (Barnes et al, 2011;Shakkottai et al, 2011), and Huntington's disease (Spampanato et al, 2008). Therefore, manipulations that may benefit neuronal function may at least be partially independent of processes that lead eventually to neuronal death in these disease models.…”
Section: Discussionmentioning
confidence: 99%